PENGARUH KEPEMILIKAN SAHAM DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Oktaviana, Leska Lely; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of share ownership and corporate social responsibility to the tax aggressiveness. This research has been conducted by using manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2011 until 2015 periods. The sample of this research has been done by using purposive sampling technique and based on predetermined criteria, 225 manufacturing companies have been selected as samples. The analysis method has been carried out by using multiple linear regressions analysis with the application of SPSS (Statistical Product and Service Solutions). The dependent variable of this research has been done by using tax aggressiveness and the independent variables i.e. share ownership consists of managerial ownership, institutional ownership, and public ownership also corporate social responsibility. The result of this research shows that managerial ownership gives significant and negative influence to the tax aggressiveness meanwhile institutional ownership gives significant and positive influence to the tax aggressiveness, public ownership gives significant and positive influence to the tax aggressiveness, and corporate social responsibility gives significant and positive influence to the tax aggressiveness.Keywords: Managerial Ownership, Institutional Ownership, Public Ownership, Corporate Social Responsibility, Tax Aggressiveness.